Deficit irrigation differently affects aroma composition in berries of Vitis vinifera L. (cvs Sangiovese and Merlot) grafted on two rootstocks. (2nd June 2022) - Palai, G.; Caruso, G.; Gucci, R.; D'Onofrio, C.
Abstract: Background and Aims: Water deficit modifies the concentration of the aroma compounds of grape berries, but little information is available on the effect of deficits applied at different phenological stages. We evaluated the effect of deficit irrigation on glycosylated volatile organic compounds (VOCs) responsible for the aroma of berries of Sangiovese and Merlot cultivars grafted on 1103P or SO4 rootstocks. Methods and Results: Vines were subjected to either pre‐ or post‐veraison water stress, and berry composition compared against that of fruit of fully irrigated vines. At harvest, a higher concentration of glycosylated VOCs was measured in berries from vines stressed pre‐veraison, but while it increased as water deficit increased in Sangiovese, this occurred only at a low or moderate level of stress in Merlot. Post‐veraison water stress had a negative or negligible effect on the concentration of glycosylated VOCs in berries at harvest. The rootstock affected the concentration of glycosylated VOCs, particularly in vines stressed pre‐veraison, with higher glycosylated VOCs observed for SO4 grafted vines than for 1103P grafted vines. Conclusions: Pre‐veraison water deficit enhanced the concentration of berry glycosylated VOCs, while post‐veraison deficit did not. The rootstock–scion interaction might amplify the irrigation effect on berry glycosylated VOCs. Significance of the Study: Modifying the timing and volume of irrigation might allow management of berry flavour for improved fruit and wine composition. Irrigation protocols should be tailored for specific cultivar–rootstock combinations.